Dinamika Sejarah, Filsafat, dan Politik Dalam Perkembangan Ilmu Konseling pada Masa Kini: Penelitian - Achsanul Hakim, Muchammad; Budiyanto, Budiyanto; Winingsih, Evi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study explores the development of counseling in Indonesia by examining its historical dynamics, philosophical foundations, and the political policies that shape its practice across educational and non-educational settings. Through an extensive literature review, the study highlights that shifts in national policy and the growing diversity of societal needs have driven counseling to expand into more complex fields, including community-based services, workplace mental health support, and public well-being programs beyond formal education institutions. Current political directions place greater emphasis on strengthening counselors’ competencies, particularly in mastering digital technologies to support the implementation of safe and accessible cybercounseling services. These developments require counselors not only to refine their technical skills but also to cultivate digital literacy, reflective abilities, and socio-cultural sensitivity in order to respond effectively to challenges across multiple service contexts. Therefore, sustained policy support, updated counselor education curricula, and comprehensive technology-oriented training are essential to ensure that counseling services continue to evolve and remain relevant in addressing the multidimensional needs of contemporary society.